Aplicação das ferramentas da qualidade na análise da viabilidade da exportação de lima ácida ‘Tahiti’ - Oliveira, Aldavi Almeida (Universidade Federal Rural do Semi-Árido, 2018)
The Acidic Lima 'Tahiti' establishes itself as one of the most important citrus species. The objective of this work was to evaluate the physical characteristics of 'Tahiti' Acid Lima fruits grafted in the semi - arid region of Ceará, more precisely in Russas. Fruits harvested at 120 days after anthesis were used. Standardized design was adopted by areas. The experimental plot consisted of one area per repetition, from which 6 fruits were used, making up 20 sample units, totaling 120 fruits. Fruit mass, fruit diameter and length, juice content and bark thickness were analyzed. The data were submitted to the analysis of international market (export) standards using the 8 main quality management tools (Pareto Diagram, Check Table, Stratification, Histogram, Cause and Effect Diagram, Dispersion Graph , Control Chart and the 5W2H action plan), however, it was identified that approximately 86.67% of the collected samples would be rejected by the export criteria, of which the fruit mass obtained a higher frequency of non-approvals (49%), followed (23%), juice content (15%), bark thickness (8%) and length (5%), respectively.
Monografia
Keywords: Ferramentas da gestão de qualidade; Exportação; Lima Ácida; Quality management tools; Export; Acid file; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA